Right to personal liberty as the basis of the principle of the inviolability of the individual in criminal proceedings (Journal of actual problems of jurisprudence, 2018)
Human rights are real as far as society is able to provide them, as far as it is interested in it. Of course, theeffect of this relationship is not exclusive: the most important role belongs to the personality, its qualities,its activity. But contrast it to society, to create the appearance of independence of the implementation of itsrights from the social environment – so obviously the possibility of the inequities in this area. Formed aninextricable link between man and the state, mediated by their mutual rights and obligations, as well as setin-law legal liability.Keywords: Personality, integrity, personal liberty, criminal procedure enforcement, preventive measures,detention, arrest, authorization, guarantee the inviolability of the person